Dampak stres kerja, kecerdasan emosional dan dukungan sosial terhadap kinerja karyawan PT XYZ - Risma Widiastuti; Susi Handayani; Siti Komariah Hildayanti (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study investigates the combined impact of work-related stress, emotional intelligence, and social support on employee performance at PT XYZ. Using a quantitative approach, data were collected via Google Forms questionnaires distributed to 95 randomly selected employees through WhatsApp. Multiple linear regression analysis revealed three key findings: (1) work-related stress positively and significantly enhances performance, suggesting that manageable stress levels may motivate employees; (2) emotional intelligence demonstrates a strong positive relationship with performance, highlighting its role in workplace effectiveness; and (3) social support significantly improves performance, emphasizing the importance of interpersonal resources. Collectively, these factors account for substantial variance in performance outcomes. The results validate theoretical expectations and offer practical insights: organizations can optimize performance by implementing stress management programs, emotional intelligence training, and robust support systems. These interventions can foster employee engagement, ultimately supporting the achievement of organizational goals